2018
DOI: 10.1021/acsnano.8b06556
|View full text |Cite|
|
Sign up to set email alerts
|

Phototheranostics: Active Targeting of Orthotopic Glioma Using Biomimetic Proteolipid Nanoparticles

Abstract: Advances in phototheranostics revolutionized glioma intraoperative fluorescence imaging and phototherapy. However, the lack of desired active targeting agents for crossing the blood–brain barrier (BBB) significantly compromises the theranostic efficacy. In this study, biomimetic proteolipid nanoparticles (NPs) with U.S. Food and Drug Administration (FDA)-approved indocyanine green (ICG) were constructed to allow fluorescence imaging, tumor margin detection, and phototherapy of orthotopic glioma in mice. By emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 64 publications
1
137
0
Order By: Relevance
“…Some literatures reported that although the tight junctions of BBB are slightly disrupted in the early stage of glioma, most nanomaterials cannot traverse the BBB to accumulate in glioma for early diagnosis and therapy. [ 8,21,22 ] In order to explore whether the metastatic cancer cell membrane‐coated nanoparticles can cross the BBB to image glioma tumor cells in the early stage, an orthotopic mouse model bearing luciferase‐expressing human glioblastoma tumor (U87MG‐Luc) was used to perform the analysis. The glioma cell activity was measured by bioluminescence imaging.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some literatures reported that although the tight junctions of BBB are slightly disrupted in the early stage of glioma, most nanomaterials cannot traverse the BBB to accumulate in glioma for early diagnosis and therapy. [ 8,21,22 ] In order to explore whether the metastatic cancer cell membrane‐coated nanoparticles can cross the BBB to image glioma tumor cells in the early stage, an orthotopic mouse model bearing luciferase‐expressing human glioblastoma tumor (U87MG‐Luc) was used to perform the analysis. The glioma cell activity was measured by bioluminescence imaging.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid growth of glioma cells into the brain can disrupt the BBB severely. [ 21 ] At 4 h after the injection of these nanoparticles, the fluorescence signals in the glioma site were found in all samples, indicating that all the four kinds of nanoparticles can diffuse through the disrupted BBB and enter into mice brains (a). This was owing to the enhanced permeability and retention effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further application of cell‐membrane coated nanomaterials is their use as highly specific imaging probes and contrasting agents. [ 96,134,141–144 ] Due to cancer cell membrane's homotypic targeting capabilities, CMNs can be used for detecting cancer with enhanced fluorescent imaging, contrasting, and detection capabilities because of lower nonspecific tissue accumulation. Fluorescent imaging is a preferred choice of imaging in biological applications but often lacks sufficient penetration depth due to the absorption and scattering of excitation light by water.…”
Section: Bolstering Cell Membrane Technology With Additional Non‐natimentioning
confidence: 99%